2021
DOI: 10.1182/bloodadvances.2021004467
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing and criteria of interim PET in DLBCL: a comparative study of 1692 patients

Abstract: Interim 18F-fluorodeoxyglucose positron emission tomography (Interim-18F-FDG-PET, hereafter I-PET) has the potential to guide treatment of patients with diffuse large B-cell lymphoma (DLBCL) if the prognostic value is known. The aim of this study was to determine the optimal timing and response criteria for evaluating prognosis with I-PET in DLBCL. Individual patient data from 1692 patients with de novo DLBCL were combined and scans were harmonized. I-PET was performed at various time points during treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 30 publications
(39 reference statements)
2
23
0
4
Order By: Relevance
“…There are no studies that looked at the predictive value of I-PET in MYC-DLBCL patients only. But these results are in line with previous studies, where MYC status was not assessed [7,8,19,20]. In our study, 28.8% of the MYC + patients had positive I-PET scans.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There are no studies that looked at the predictive value of I-PET in MYC-DLBCL patients only. But these results are in line with previous studies, where MYC status was not assessed [7,8,19,20]. In our study, 28.8% of the MYC + patients had positive I-PET scans.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, 28.8% of the MYC + patients had positive I-PET scans. This PET-positivity rate was comparable with the PET-positivity rate of MYC - patients (23.8%), and with PET-positivity rates reported in a recent individual patient data analysis [ 8 ]. However, Dunleavy and colleagues reported that 70.8% of MYC + DLBCL patients treated with dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab (EPOCH-R) were PET positive after two cycles of treatment [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Standard first-line immunochemotherapy consists of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). About two-thirds of DLBCL patients achieve long-term disease-free survival by R-CHOP, whereas the other one-third have a poor prognosis and low response rates to salvage treatment ( 7 ).…”
Section: Introductionmentioning
confidence: 99%